Implementasi Kebijakan Dana Bantuan Operasional Sekolah Di Kabupaten Mamuju Tengah - Rahmawaty, Sukma; Madani, Muhlis; Haerana, Haerana (Universitas Muhammadiyah Makassar, 2024)
The research objective was to determine the implementation of the School Operational Assistance Fund policy at SD INP Bambamanurung based on Edward III's theory. The type of research used is a descriptive type with a qualitative approach. The results of the study show that of the four indicators, the steps taken by the Government in managing BOS funds have been going well, seen from communication that conveys information directly, adequate human resources, disposition and bureaucratic structure that are in accordance with established standards. , but there are still some deficiencies due to inhibiting factors in the form of a lack of adequate facilities obtained by traders and the community as those who are affected by this policy.